THE PRACTICE OF BUYING AND SELLING ONLINE GAMES ACCORDING TO FIQH MUAMALAH: Study in Valorant Game Account - Sultan Farizi Lidyan; Hasnul Arifin Melayu (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
This study aims to analyze the practice of buying and selling online game accounts, specifically in the game Valorant, from the perspective of Islamic commercial jurisprudence (fiqh muamalah). With the growing popularity of online games among the younger generation, account trading has become a common phenomenon, although it is conducted outside the official channels provided by game developers. This research employs a qualitative descriptive approach, utilising data collection methods such as interviews, observations, and a literature review. The findings reveal that the buying and selling of Valorant accounts are conducted informally, without legal protection, and do not meet the pillars and conditions required for a valid sale in Islam. The practice involves several risks, including fraud, account reclamation by the seller (hack back), account banning by Riot Games, and value uncertainty due to the gacha system. From the fiqh muamalah perspective, such transactions are deemed problematic as they involve elements of gharar (uncertainty), ghisy (fraud), and lack of complete ownership (milkiyyah tammah). Therefore, the trading of Valorant accounts is not in accordance with Islamic commercial principles and should be avoided by Muslims.